Declassified protocols indicate Golda Meir considered Palestinian statehood - Staff, Toi (The Times of Israel, 2023)
Documents show that former prime minister gave serious thought to possibility of formation of a Palestinian entity, despite public comments.
Keywords: 2023-08 August; Golda Meir; Palestine; Palestinian Statehood